Pendampingan Pemanfaatan Akun Marketplace bagi Pengusaha Kuliner Berbahan Dasar Ikan Lele Kelompok Poklahsar Srikandi: Assistance in Utilizing Marketplace Accounts for Culinary Entrepreneurs Based on Catfish, Poklahsar Srikandi Group - Setiaji, Cahyo Apri; Ngalim, Muhammad; Abadi, Bayu; Ramadhani, Kayla Nazwa; Anjani, Nesi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The group of culinary entrepreneurs who are members of Poklahsar Srikandi, located in Maron Village, Loano District, Purworejo Regency, have dry and wet food products made from processed catfish meat. However, they experience difficulties in selling products due to limited marketing strategies, especially online. Community Service (PKM) regarding training and assistance in creating marketplace accounts aims to increase knowledge and skills in using online sales accounts. The training methods used are lectures to deliver material, clinical discussions, and mentoring training. There were 35 participants, consisting of 15 men and 20 women. The result of this Community Service (PKM) activity is an increase in participants' knowledge about the marketplace and their utilization skills to increase product sales turnover. Another result is the formation of an independent marketplace sales account. The marketplace allows them to market these culinary products effectively and efficiently, without being limited by distance and time.